Collaboration and integrated water resources management: A literature review. Issue 2 (28th November 2019) - Galvez, Victor; Rojas, Rodrigo
Abstract: Collaboration has been widely recognized as a critical driver for the achievement of Integrated Water Resources Management (IWRM) outcomes; aiming at safeguarding economic, social, and environmental interests within a basin. This paper reviews research on collaboration and its relationship with IWRM. It focuses on the following aspects: (a) when collaboration is needed; (b) frameworks of collaboration; (c) benefits and costs; (d) stakeholder engagement and collaboration; and (e) stakeholder engagement mechanisms for an IWRM. This research reinforces that collaboration has been recognized internationally by multiple agencies and authors as a critical element for IWRM. However, most of the research on collaboration has been focused more on qualitative rather than quantitative aspects, with a special emphasis on benefits over costs. Therefore, future research can further analyze the costs and benefits under a quantitative perspective, in order to evaluate and understand the impact of a collaborative process and support decisions about to what extent collaboration should be undertaken. 摘要: 协作被广泛认为是水资源综合管理（IWRM）结果成就的关键驱动力；（IWRM）旨在保护流域中的经济利益、社会利益和环境利益。本文对协作及协作与IWRM的关系进行了文献综述。本文聚焦于以下方面：（1）何时需要协作；（2）协作框架；（3）收益与成本；（4）利益攸关方的参与及协作；（5）一项IWRM中利益攸关方的参与机制。本研究巩固了"协作被全球多个机构和作者视为IWRM的关键要素"这一主张。然而，关于协作的大多数研究更多地聚焦于定性方面，而不是定量方面，且尤其强调收益与成本。因此，未来研究能从定量的视角进一步研究成本与收益，以期对协作过程的影响进行评价和理解，并对关于协作程度应是多少的决策进行支持。 Resumen: La colaboración ha sido ampliamente reconocida como un impulsor crítico para el logro de los resultados de la Gestión Integrada de los Recursos Hídricos (GIRH); con el objetivo de salvaguardar los intereses económicos, sociales y ambientales dentro de una cuenca. Este artículo revisa la investigación sobre la colaboración y su relación con la GIRH. Se centra en los siguientes aspectos: (1) cuando se necesita colaboración; (2) marcos de colaboración; (3) beneficios y costos; (4) participación y colaboración de las partes interesadas; y (5) mecanismos de participación de los interesados ​​para una GIRH. Esta investigación refuerza que la colaboración ha sido reconocida internacionalmente por múltiples agencias y autores como un elemento crítico para la GIRH. Sin embargo, la mayor parte de la investigación sobre colaboración se ha centrado más en aspectos cualitativos que cuantitativos, con un énfasis especial en los beneficios sobre los costos. Por lo tanto, la investigación futura puede analizar aún más los costos y beneficios bajo una perspectiva cuantitativa, con el fin de evaluar y comprender el impacto de un proceso de colaboración y apoyar las decisiones sobre hasta qué punto se debe llevar a cabo la colaboración.